PENGEMBANGAN EVALUASI PEMBELAJARAN BAHASA INDONESIA BERBASIS TAKSONOMI STRUCTURE OF OBSERVED LEARNING OUTCOME - Subyantoro Subyantoro (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe characteristics and principles of the development of evaluation kits based on the taxonomy of the Structure of Observed Learning Outcome (SOLO) in the Bahasa Indonesia subject and to test the effectiveness. It employed a research and development design. It was conducted up to the seventh stage, namely operationalproduct revision, a revision after obtaining feedback from field testing. The results of the study are as follows. First, the characteristics of the evaluation kits include item types, time allocation, tasks, critical thinking skills, and problem solving skills. Second, the principles of the development of evaluation kits include appropriate item types, tasks,critical thinking skills, and problem solving skills. Third, the evaluation kits consist of conceptual materials, evaluation grids, item cards, test packages and instructions, and answer keys accompanied by assessment and scoring rubrics. Fourth, the effectiveness of the evaluation kits is indicated by the test validity and reliability and the item difficulty index and discrimination index.